Access to and control over resources in urban agriculture in Tamale, Ghana - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Nchanji, Yvonne Kiki (Academic Press, 2022)
Urban and Regional Agriculture: Building Resilient Food Systems explores the sustainable integration of food provision, distribution and consumption through urban farms, agricultural systems, user communities and structural facilities designed to optimize food production and consumption. The book addresses the fundamental and pressing challenges of urban planning problems, waste minimization, food sourcing, access and equity issues, and multiple land use optimization. Sections cover the need and opportunities of urban agriculture, discuss tradition and transition, space and regulatory topics, explore the range of urban agriculture options (aquaculture to urban permaculture), discuss support structures and constructs of physically creating urban agricultural areas, and much more. Edited and authored by leading experts in the field, this volume will be valuable for those working to address issues of food security in urban environments.